2017
DOI: 10.1155/2017/3925868
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of Acinetobacter baumannii Isolates for Metallo-β-Lactamases and Extended-Spectrum-β-Lactamases Genes in Intensive Care Unit, Mansoura University Hospital, Egypt

Abstract: Acinetobacter baumannii (A. baumannii) has been known as a causative pathogen of hospital acquired infections. The aim of this study is to examine the presence of A. baumannii among clinical isolates from intensive care unit (ICU) in Mansoura University Hospital (MUH), its antibiotic resistance pattern, and prevalence of antibiotic resistance genes metallo-β-lactamases (MBLs) and extended-spectrum-β-lactamases (ESBLs) among A. baumannii isolates. A. baumannii was identified by colony morphology, API 20E, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
27
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 29 publications
12
27
8
Order By: Relevance
“…Carbapenem insensitivity was detected in 70.8% (34/48) of collected isolates, which is similar to other studies carried in Egypt by Sultan and Seliem [24]. Others have shown a higher prevalence for CRAB reaching 90% [10,25,26], which suggests that Egypt is the topmost country in the region in CRAB prevalence [27]. CRAB treatment typically relies on other last-resort antibiotics such as colistin and tigecycline and sometimes antibiotic combinations [28].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Carbapenem insensitivity was detected in 70.8% (34/48) of collected isolates, which is similar to other studies carried in Egypt by Sultan and Seliem [24]. Others have shown a higher prevalence for CRAB reaching 90% [10,25,26], which suggests that Egypt is the topmost country in the region in CRAB prevalence [27]. CRAB treatment typically relies on other last-resort antibiotics such as colistin and tigecycline and sometimes antibiotic combinations [28].…”
Section: Discussionsupporting
confidence: 83%
“…High prevalence of bla NDM gene (67.7% of CRAB isolates) was observed in our study compared to previous studies carried out in Egyptian hospitals which showed bla NDM prevalence of 8% [40] and 39.3% [25] among CRAB isolates. The bla NDM-1 and bla NDM-2 -encoding genes were first described in A. baumannii isolated from Egyptian patients [41] and then a noteworthy spread of bla NDM -positive A. baumannii was detected in the Middle East [42].…”
Section: Discussioncontrasting
confidence: 65%
“…They hydrolyze all penicillins and cephalosporins with the exception of cephamycins [128]. CTX-M, GES, PER, SCO, SHV, TEM, and VEB are among identified class A β-lactamases in A. baumannii [129][130][131][132]. While some of these, like SCO-1 and TEM-1, are narrow-spectrum, others like CARB-10, CTX-M-2, CTX-M-15, GES-14, PER-1, PER-7, and SHV-5 are extended spectrum β-lactamases (ESBLs) [133,134].…”
Section: Ambler Class a Enzymesmentioning
confidence: 99%
“…accounted for 95.7%. However, the authors didn't investigate blaNDM among the studied isolates (21). Another Egyptian study has detected blaNDM among 66.7% of 50 A.baumannii isolates.…”
Section: Discussionmentioning
confidence: 94%